2011
DOI: 10.2337/db11-0132
|View full text |Cite|
|
Sign up to set email alerts
|

β-Cell Uncoupling Protein 2 Regulates Reactive Oxygen Species Production, Which Influences Both Insulin and Glucagon Secretion

Abstract: OBJECTIVEThe role of uncoupling protein 2 (UCP2) in pancreatic β-cells is highly debated, partly because of the broad tissue distribution of UCP2 and thus limitations of whole-body UCP2 knockout mouse models. To investigate the function of UCP2 in the β-cell, β-cell–specific UCP2 knockout mice (UCP2BKO) were generated and characterized.RESEARCH DESIGN AND METHODSUCP2BKO mice were generated by crossing loxUCP2 mice with mice expressing rat insulin promoter-driven Cre recombinase. Several in vitro and in vivo pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
126
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 53 publications
3
126
1
1
Order By: Relevance
“…UCP2 activity and expression are associated with negative regulation of insulin secretion. Knock-out of UCP2 expression or inhibition of UCP2 function with genipin increases GSIS from pancreatic islets, observations that have been replicated in INS-1E cells (7)(8)(9). The putative signaling function of UCP2 is thought to stem from its capacity to control mitochondrial ROS emission (reviewed in Ref.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…UCP2 activity and expression are associated with negative regulation of insulin secretion. Knock-out of UCP2 expression or inhibition of UCP2 function with genipin increases GSIS from pancreatic islets, observations that have been replicated in INS-1E cells (7)(8)(9). The putative signaling function of UCP2 is thought to stem from its capacity to control mitochondrial ROS emission (reviewed in Ref.…”
mentioning
confidence: 99%
“…10). For instance, using a cell-specific UCP2 deletion mouse model, Robson-Doucette et al (9) demonstrated that ␤ cell UCP2 has little effect on mitochondrial ATP production, but it significantly contributes to the control of mitochondrial ROS production, which in turn regulates GSIS. In support of this, various reports have shown that exposing ␤ cells (either insulinoma cells or in pancreatic islets) to low amounts of superoxide (O 2 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The mitochondrion is one major source of intracellular ROS and the uncoupling proteins (UCPs), a superfamily of mitochondrial anion transporters, are important natural antioxidants in controlling cellular ROS homeostasis (Chan et al, 2010). Among them, UCP2 contributes to the control of mitochondrial ROS production, thus preventing oxidative stress (Robson-Doucette et al, 2011). Enhanced GSIS and increased intracellular ROS have been found in both islet cells of UCP2-deficient mice (Zhang et al, 2001;Lee et al, 2009) and INS-1E cells (Affourtit et al, 2011) and lean mouse islets (Saleh et al, 2006) with UCP2 knockdown.…”
Section: Introductionmentioning
confidence: 99%